CIRA final report 2001-2010 - Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 2010)
This report describes research funded in collaboration with NOAA's cooperative agreement and the CIRA Joint Institute contract period July 1, 2001 through June 30, 2010.
Cooperative Institute for Research in the Atmosphere final report 2001-2010
Keywords: Colorado State University. Cooperative Institute for Research in the Atmosphere